. The Utilization of Cocoa Pod Husk on Process Alkalization Nib (Seed Meet) Cocoa and Effect on Quality Cocoa Powder - Neni Cahyati; Eko Heri Purwanto; Selly Harnesa Putri (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
The problem facing the industry of cocoa powder in Indonesia is that cocoa powder on the market has a high fat content, high acidity, a color quality that is not comparable with imported cocoa products, and a variety of flavors and aromas. Alkalization is a method that can handle these problems. Alkalization is a process to improve the quality and appearance of cocoa powder. Alkalization is carried out by adding potassium, magnesium, and others to cocoa. High potassium content can be found in cocoa pod husks. Cocoa pod husks are the main by-product from the cocoa industry, constituting 67 – 76% of the cocoa fruit weight. Cocoa pod husk contains potassium, fiber, and antioxidants that function as biomaterials for food and non-food products. The aims of the study were to determine and evaluate the quality of cocoa powder with the effect of alkalization treatments using cocoa pod husks. The study was carried out at The Indonesian Industrial and Beverage Crops Research Institute, Sukabumi, West Java, from January to June 2022. This study was designed in a factorial completely randomized design. The first factor was the alkaline material, which consisted of two levels (cocoa pod husk and baking soda). The second factor was the concentration, which consisted of 3 levels (1%, 2%, and 3%). The variables observed were the L*, a*, b*, moisture content, ash content, fineness, pH, fat content, protein, antioxidant activity, and organoleptic properties. The results showed that the alkalization process with alkaline material from cocoa pod husk and a concentration of 2% is the best quality characteristic of cocoa powder in accordance with SNI 01-3747-2013.